Evaluating the Efficacy of Standing Committees in Resource Allocation and Service Delivery in Local Government: : Evidence from Zila Parishad - Sheikh, Jahid Hasan; Hossain, Md. Al-Amin (The Jahangirnagar Review, 2025)
The Zila Parishad (ZP) is the highest and oldest unit of rural local government in Bangladesh. Standing committees of ZP plays crucial role to ensure service delivery and resources allocation in local communities. Understanding their efficacy is essential for effective local governance. However, previous studies have rarely examined these issues systematically. This paper follows descriptive analysis. The main object of this qualitative study is to explore the role of standing committee in terms of resources allocation and service delivery in zila parishad. Data are generated from In-depth interview (IDI), Focus Group Discussion (FGD) and secondary resources such as books, journal article, ZP office documents, newspaper etc. The analysis shows standing committees of ZP are not effective in terms of service delivery and resource allocation. Excessive control by ZP chairman, lack of funding and dependency on government officials of ZP are the main obstacles in ensuring efficacy. The findings suggest that decentralizing decision-making process, ensuring accountability and transparency can improve the current situation.